2021
DOI: 10.1002/ceat.202000368
|View full text |Cite
|
Sign up to set email alerts
|

Catalyzed Sintering of Regenerated CaO Induced by Partition Evolution of Calcium Carbonate

Abstract: The partition evolution of parent calcium carbonate (CaCO3) and its effect on the catalyzed sintering of regenerated CaO during calcium looping cycles were investigated. The carbonation reaction rate has a heterogeneous distribution either in the particle radial direction or in the same layer, which causes the partition structure evolution of CaCO3 from overall dense structure to region partition structure. Both the residual and sintering of regenerated CaO were enhanced with the structural evolution of carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The sintering effect occurs at high calcination temperatures, reducing the carbonation conversion of sorbent inside the carbonator reactor and leading to a high degradation rate. In addition to attrition and the sintering effect, some of the degradations can be related to the closure of pores smaller than 300 nm [ 57 ] during carbonation that does not reopen during the subsequent cycles [ 34 ]. This degradation makes the sorbent unable to maintain the stability of the sorption performance after many cycles.…”
Section: Calcium Loopingmentioning
confidence: 99%
“…The sintering effect occurs at high calcination temperatures, reducing the carbonation conversion of sorbent inside the carbonator reactor and leading to a high degradation rate. In addition to attrition and the sintering effect, some of the degradations can be related to the closure of pores smaller than 300 nm [ 57 ] during carbonation that does not reopen during the subsequent cycles [ 34 ]. This degradation makes the sorbent unable to maintain the stability of the sorption performance after many cycles.…”
Section: Calcium Loopingmentioning
confidence: 99%
“…Limestone with about 95.7 % CaCO 3 purity from Donggang quarry (Liaoning, China) was used in this research, and the chemical components which were reported in a previous work [46]. Limestone powders in the size ranges of 0.04-0.08 and 0.15-0.18 mm were obtained by sieving.…”
Section: Preparation Of Sorbentsmentioning
confidence: 99%